"Doing the Right and the Good": Thinking Against Mass Incarceration. Issue 1 (26th May 2022) - Cohen, Aryeh
ABSTRACT: In 1952, Rabbi Eliezer Yehudah Waldenberg (a member of the Supreme Rabbinical Court of Israel) and Rabbi Ben Zion Meir Chai Uziel (the Rishon LeTziyon and Sephardic Chief Rabbi of Israel) addressed the question of incarceration in a Jewish state according to the halakhic tradition. A generation later, Rabbi Chaim David Halevi the Chief Rabbi of Tel Aviv‐Yaffo) also addressed this question. Their approaches shed light on the way we should be thinking about incarceration in general, and the overwhelming problem of the current moment in the United States: mass incarceration.